Essential manual of 24 hour blood pressure management : from morning to nocturnal hypertension - Kario, Kazuomi (Hoboken, NJ : Wiley-Blackwell, 2022)
"Blood pressure (BP) always varies over time, including beat-by-beat, trigger-induced, orthostatic, diurnal, day-by-day, weekly, seasonal, and age-related variations. Of these different BP variability components, circadian rhythm is the central component of individual BP variability, and there is a large body of accumulating evidence highlighting the importance of this parameter. Basic circadian rhythm forms the basis of individual diurnal BP variation (Figure 1.1) 1. The circadian rhythm of BP is physiologically determined partly by the intrinsic rhythm of central and peripheral clock genes, which regulate the neurohumoral factor and cardiovascular systems, and partly by the sleep-wake behavioral pattern, and is associated with various pathological conditions. In addition to different patterns of circadian rhythm, short-term BP variability such as morning BP surge (MBPS), physical or psychological stress-induced daytime BP, and nighttime BP surge triggered by hypoxic episodes in obstructive sleep apnea, arousal, rapid-eye-movement sleep, and nocturnal behavior (e.g. nocturia) modulates the circadian rhythm of BP, resulting in the different individual diurnal BP variation"--
Evidence and scientific rationale for ambulatory blood pressure monitoring (ABPM) -- Scientific rationale for HBPM -- Practical use of ABPM and HBPM -- BP targets, when to initiate antihypertensive therapy, and non-pharmacological treatment -- Antihypertensive medication -- Renal denervation -- Blood pressure linked telemedicine and telecare -- Asia Perspectives
BIBINDX
Keywords: Blood pressure -- Measurement; Blood pressure -- Regulation; Hypertension -- drug therapy; Blood Pressure Monitoring, Ambulatory; Blood Pressure -- physiology; Blood Pressure Determination; Circadian Rhythm -- physiology; Electronic books